2002
DOI: 10.1677/joe.0.1730407
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor-alpha and -beta are expressed throughout postnatal development in the rat and rabbit growth plate

Abstract: Estrogen regulates skeletal growth and promotes epiphyseal fusion. To explore the mechanisms underlying these effects we investigated the expression of estrogen receptor-(ER ) and -(ER ) in rat and rabbit growth plates during postnatal development, using immunohistochemistry. Immunoreactivity for ER and ER was observed in resting zone and proliferative zone chondrocytes at all ages studied for both rat (7, 14, 28 and 70 days of age) and rabbit (1, 7, 28 and 120 days of age). In the rat distal humerus and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 46 publications
3
34
0
1
Order By: Relevance
“…Previous studies found that ovariectomy accelerates, while subsequent high dose of estrogen administration suppresses, long bone growth (Silberberg and Silberberg 1971;Nilsson et al 2002;Chagin et al 2004;. This was confi rmed in the present study in that the heights of the growth plates and overall lengths of the femurs were greatest in the ovariectomized group.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Previous studies found that ovariectomy accelerates, while subsequent high dose of estrogen administration suppresses, long bone growth (Silberberg and Silberberg 1971;Nilsson et al 2002;Chagin et al 2004;. This was confi rmed in the present study in that the heights of the growth plates and overall lengths of the femurs were greatest in the ovariectomized group.…”
Section: Discussionsupporting
confidence: 88%
“…Ovariectomy with or without subsequent estrogen injection has been one of the major methodologies for investigating the effect of the female hormone, and several types of animals have been used for this method (Silberberg and Silberberg 1971;Weise et al 2001;Nilsson et al 2002Nilsson et al , 2003. In rabbits, sexual maturation starts around four months after birth (Suzuki et al 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemistry was performed as described elsewhere (Nilsson et al 2002). The primary rabbit polyclonal anti-IGF1 (H-70) antibody was purchased from Santa Cruz Biotechnology (Santa Cruz, CA, USA) and used at a dilution of 1:100 (Chagin et al 2006, Shao et al 2007.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…ER· and ERß have been located in several mammalian growth plates including the human (6,28,29) and articular cartilage (30). The presence of ER is an important requirement for in vitro studies on the mechanisms of estrogen action on growth.…”
Section: Discussionmentioning
confidence: 99%